2018
DOI: 10.21873/anticanres.12222
|View full text |Cite
|
Sign up to set email alerts
|

Phenoxodiol Increases Cisplatin Sensitivity in Ovarian Clear Cancer Cells Through XIAP Down-regulation and Autophagy Inhibition

Abstract: PXD increased cisplatin sensitivity through XIAP down-regulation and autophagy inhibition and could be a new candidate for ovarian clear cell carcinoma treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 23 publications
(33 reference statements)
1
16
0
Order By: Relevance
“…GO and KEGG analyses indicated that the differentially expressed ARGs were mainly enriched mainly in platinum drug resistance. Studies have shown that the induction of autophagy in cancer can increase cisplatin resistance (25,26), consistent with our results, suggesting that these ARGs can promote the progression of ccRCC through platinum drug resistance. However, further experiments are needed to verify the role of autophagy in ccRCC.…”
Section: Discussionsupporting
confidence: 92%
“…GO and KEGG analyses indicated that the differentially expressed ARGs were mainly enriched mainly in platinum drug resistance. Studies have shown that the induction of autophagy in cancer can increase cisplatin resistance (25,26), consistent with our results, suggesting that these ARGs can promote the progression of ccRCC through platinum drug resistance. However, further experiments are needed to verify the role of autophagy in ccRCC.…”
Section: Discussionsupporting
confidence: 92%
“…Hydrochloroquine (HCQ) is a less toxic derivative of CQ with similar clinical applications. HCQ cellular effects are similar to those of CQ and consistently its was shown to possess CPT chemosensitizing properties in vitro [46,47,49]. 33.…”
Section: Chloroquine and Its Derivativesmentioning
confidence: 80%
“…The molecular mechanism of PXD action was suggested to involve X-linked inhibitor of apoptosis protein (XIAP) and FLICE inhibitory protein (FLIP) downregulation as well as direct inhibition of topoisomerase II and ENOX2 (ecto-NOX disulfide-thiol exchanger 2). PXD was shown to sensitize ovarian cancer cell line towards CPT [47,85]. This was accompanied by XIAP downregulation and autophagy inhibition with Beclin-1 inhibition.…”
Section: Phenoxofiolmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, Miyamoto et al reported that phenoxodiol, a synthetic analogue of the plant isoflavone genistein with an improved anticancer efficacy (0.5-2 µg/mL), inhibited autophagy and X-linked inhibitor of apoptosis protein (XIAP), thus sensitizing ovarian clear cell carcinoma cells (KK cells) to cisplatin treatment [191].…”
Section: Isoflavonesmentioning
confidence: 99%